Pre-service teachers' self-regulated learning and time perspective - Romulo, Oliver M.
This study investigated how the Filipino pre-service teachers demonstrated self-regulated learning and time perspective during the COVID-19 pandemic using a mixed-methods sequential explanatory design. The self-regulated learning mean score of 3.22 suggested that respondents were self-regulated learners, whereas the deviation from the balanced time perspective (DBTP) of 2.69 indicated that they were poorly adapted to their situation and had a fatalistic outlook on life. The mean scores of 3.80 in the aversive view of the past (Past-Negative), 3.73 in seeking thrill and pleasure (Present-Hedonistic), and 3.05 in the belief of future predestination (Present-Fatalistic) were more than the mean scores of 3.01 in striving for goals and rewards (Future) and 2.95 in the sentimental view of the past (Past-Positive). These DBTP and time perspective scores suggested temporal disintegration where their past and future seem to have collapsed into the present. Respondents were presently drawn on bad memories from the past while they were pursuing goals. The study also examined how the self-regulated learning and time perspective components relate to one another. Findings revealed that Future significantly predicted and had the largest positive effect on all self-regulated learning attributes. Furthermore, canonical correlation analysis validated the functions of Boekaerts’ Dual Processing Model. The Future, Past-Positive, and all self-regulated learning attributes were to increase knowledge and skills, whereas the Present-Hedonistic, Past-Positive, Present-Fatalistic, self-evaluation, seeking assistance, and memory strategy attributes were to maintain wellbeing. Respondents were switching between these functions. It was therefore recommended to develop an instrument capable of evaluating these dual aspects simultaneously and initiate cross-cultural comparative studies to explore similarities and differences in self-regulated learning processes and time perspective manifestations across diverse cultural contexts.